On Submersion of CR-Submanifolds of l.c.q.K. Manifold. (28th November 2012) - Choudhary, Majid Ali; Matehkolaee, Mahmood Jaafari; Jamali, Mohd.
Abstract : We study submersion of CR-submanifolds of an l.c.q.K. manifold. We have shown that if an almost Hermitian manifold B admits a Riemannian submersion π : M → B of a CR-submanifold M of a locally conformal quaternion Kaehler manifold M ¯, then B is a locally conformal quaternion Kaehler manifold.